(untitled) (Jurnal Psikologi Udayana, 2015)
Student is a learner who has moral duties in applying Tri Dharma Perguruan Tinggi consisted of three important missions, which are implementing education, research, and community service. One embodinent of community service is being involved in the organizational activities around campus. Student activists have an immense relation with the role of emotional intelligence since they have more responsibilities than those who are not actively participating in organisation. In addition to running the missions of Tri Dharma Perguruan Tinggi, students would also encounter personal problem and be faced with school’s demands. The purpose of conducting this research is to investigate the correlation of emotional intelligence and academic achievement of student organization activists at University of Udayana. The sampling technique used in this research was simple random sampling. Subjects were 129 student activists at University of Udayana, age ranged from 17 to 25 years old. Emotional intelligence scale was deployed based on emotional intelligence aspects proposed by Goleman (2002). Transcripts were also collected to determine academic achievement of the subjects, aside from spreading the emotional intelligence scale. Karl Pearson product-moment correlation analysis was conducted to observe correlation of emotional intelligence and academic achievement. Correlation coefficient value obtained from the result of analysis performed on the variables, emotional intelligence and academic achievement, were -0.204 and P of 0.021 (p<0.05). This result shows that there is a negative relationship between emotional intelligence and academic achievement, which also indicates that the increase of emotional intelligence is followed by the decrease of academic achievement on student organization activists. The number of organizations in which the subjects participated in, various activities performed outside campus, and other external factors of research’s subjects contributed to the effect of academic achievements. Keyword: emotional intelligence, academic achievement, student organization activists.